Language Support for Fast and Reliable Message-based Communication in Singularity OS - Fahndrich, Manuel; Aiken, Mark; Hawblitzel, Chris; Hodson, Orion; Hunt, Galen; Larus, Jim; Levi, Steven (Proceedings of the EuroSys 2006 Conference, 2006)
Message-based communication offers the potential benefits of providing stronger specification and cleaner separation between components. Compared with shared-memory interactions, message passing has the potential disadvantages of more expensive data exchange (no direct sharing) and more complicated programming. In this paper we report on the language, verification, and run-time system features that make messages practical as the sole means of communication between processes in the Singularity operating system. We show that using advanced programming language and verification techniques, it is possible to provide and enforce strong system-wide invariants that enable efficient communication and low-overhead software- based process isolation. Furthermore, specifications on communication channels help in detecting programmer mistakes early—namely at compile-time—thereby reducing the difficulty of the message-based programming model. The paper describes our communication invariants, the language and verification features that support them, as well as implementation details of the infrastructure. A number of benchmarks show the competitiveness of this approach.
Best Paper